Learning environment and school readiness of preschool-age children - Santos, Elizabeth Reyes (2008)
The study sought to analyze the child's early learning environments--the home, media, and peer group-- and their influence on the school readiness skills of pre-school children. This is a descriptive research study that looked into the profile of the child's school readiness in physical, social, cognitive, and language aspects. Participants in this study are children aged 3-5 years old who have not attended formal schooling neither in day care center nor in kindergarten. The study reaffirmed the previous research findings that the home has a great influence in the school readiness based on variables such as parent-adult shared reading, verbal interaction with significant others, family outings, and their educational aspirations for children. Likewise, the provision of broadcast and print media contributed to the development of language and receptive skills due to the stimulation of the visionary and auditory senses.